All-Inside Meniscus Ramp Repair: Ramp Repair From Anterior Portals - Salim Al Habsi, M.D.; Jhulia Kawachi Cruz, M.D., D.P.B.O., M.B.A.; Mok Ying Ren, M.B.B.S., F.R.C.S.; Lee Yee Han Dave, M.B.B.S., F.R.C.S. (Arthroscopy Techniques)
Ramp lesions are defined as the meniscocapsular separation of the posterior horn of the medial meniscus, and they are commonly seen in association with anterior cruciate ligament (ACL) tear. They often are missed and, therefore, a high index of suspicion should be raised in ACL tears with high-grade knee laxity and ACL graft failures. Most described ramp repair techniques are performed through the posteromedial portal in addition to standard anterior portals. However, use of the posteromedial portal increases surgical time, requires the use of special instruments, and has a steep learning curve. We present our technique of repairing meniscus ramp tears with all-inside meniscal repair devices, assisted with percutaneous medial release and using only the standard anteromedial and anterolateral portals. Our technique is simple, effective, and reproducible for arthroscopic knee surgeons.